A Review on Levering Technology for Sustainable Development in Agricultural Extension Program - , Ramesh Chand Bunkar; , Ananda K R; , Kapil Kumar; , Baisakhee Sadangi; , Bandana Shahu Gupta; , D R K Saikanth; , Anoop Shukla (Archives of Current Research International, 2024)
The transformative potential of technology in agricultural extension programs and its implications for sustainable development. By integrating technologies such as artificial intelligence (AI), machine learning, blockchain, and precision farming tools, agricultural practices can be significantly improved in terms of efficiency, productivity, and sustainability. The discussion is organized into a comprehensive framework that examines successful implementations and outcomes in both developed and developing regions, highlighting case studies that demonstrate the beneficial impacts of technology on farming. Key challenges such as the digital divide, financial constraints, policy and regulatory hurdles, and environmental considerations are critically analyzed to understand the barriers to technology adoption and effective integration. Recommendations are made for policy adjustments, the deployment of inclusive technology strategies, and considerations for long-term sustainability to ensure that these technological advancements contribute effectively to global food security and adhere to Sustainable Development Goals (SDGs). Additionally, future directions are suggested, focusing on emerging technologies like next-generation biotechnologies and their potential impacts. The paper concludes that while the introduction of innovative technologies in agricultural extension holds great promise for transforming agricultural practices, a balanced approach is required. This approach should not only embrace technological innovation but also address the socio-economic and environmental challenges associated with technology adoption. Through strategic policy frameworks, tailored technology solutions, and ongoing support for capacity building, technology can be effectively leveraged to enhance agricultural productivity and sustainability, thereby supporting the broader objectives of economic stability, environmental stewardship, and social equity in rural communities worldwide. The insights provided in this paper are intended to guide policymakers, stakeholders, and practitioners in the agricultural sector towards more effective and sustainable integration of technology in agricultural extension services.